2010
DOI: 10.1096/fj.09-154344
|View full text |Cite
|
Sign up to set email alerts
|

The neuroretina is a novel mineralocorticoid target: aldosterone up‐regulates ion and water channels in Müller glial cells

Abstract: Glucocorticoids reduce diabetic macular edema, but the mechanisms underlying glucocorticoid effects are imperfectly elucidated. Glucocorticoids may bind to glucocorticoid (GR) and mineralocorticoid (MR) receptors. We hypothesize that MR activation may influence retinal hydration. The effect of the MR agonist aldosterone (24 h) on ion/water channel expression (real-time PCR, Western blot, immunofluorescence) was investigated on cultured retinal Müller glial cells (RMGs, which contribute to fluid homeostasis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 42 publications
1
119
0
7
Order By: Relevance
“…However, we cannot exclude the possibility that MCR signaling influences the formation of MGPCs. Although the MCR-preferring ligand aldosterone failed to influence FGF2/MAPK signaling in Müller glia and did not influence the proliferation of MGPCs in damaged retinas, the GCRpreferring agents that we used are known to have some affinity for MCR (Robertson et al, 2010) and MCR is likely to be expressed by Müller glia (Zhao et al, 2010). Consistent with our findings, a recent report by Anacker and colleagues (Anacker et al, 2013) indicates that low levels of cortisol, acting through MCR, increased proliferation of hippocampal progenitors and decreased neuronal differentiation whereas high levels of cortisol, acting through GCR, decreased proliferation and decreased neural differentiation.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, we cannot exclude the possibility that MCR signaling influences the formation of MGPCs. Although the MCR-preferring ligand aldosterone failed to influence FGF2/MAPK signaling in Müller glia and did not influence the proliferation of MGPCs in damaged retinas, the GCRpreferring agents that we used are known to have some affinity for MCR (Robertson et al, 2010) and MCR is likely to be expressed by Müller glia (Zhao et al, 2010). Consistent with our findings, a recent report by Anacker and colleagues (Anacker et al, 2013) indicates that low levels of cortisol, acting through MCR, increased proliferation of hippocampal progenitors and decreased neuronal differentiation whereas high levels of cortisol, acting through GCR, decreased proliferation and decreased neural differentiation.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, Dex, CpdA and RU486 act at the MCR, albeit with low affinity (Robertson et al, 2010). In addition, the MCR is known to be expressed by Müller glia in the rat retina (Zhao et al, 2010). Thus, we tested whether Mcr expression was affect by NMDA treatment, and whether the MCR-preferring ligand aldosterone influences the formation of MGPCs in NMDA-damaged retinas.…”
Section: Müller Glia (Data Not Shown) By Contrast Injections Of Dex Ormentioning
confidence: 99%
“…5,7,23,38 The presence of aldosterone synthase, MR, and 11␤HSD2 in glia and ganglion cells is also of interest given the contribution of these cell types to OIR 35,36 and recent evidence that aldosterone influences ion and water channels in macroglial Müller cells. 39 In conclusion, inhibition of aldosterone synthase is equally effective at reducing the retinal neovascularization of OIR as ARB, a finding that highlights the potential of inhibiting aldosterone for the treatment of neovascular retinopathies. Whether FAD286 is as protective as ARB in other aspects of retinal pathology, such as reducing intraocular pressure, 40,41 is worth investigating in future studies.…”
Section: Deliyanti Et Al Aldosterone and Retinal Neovascularizationmentioning
confidence: 80%
“…Emerging evidence indicates that aldosterone is likely to influence retinal pathology, such as neovascularization, and also normal physiological processes, such as retinal fluid homeostasis. 39 We now await the findings of future studies to elucidate the contribution of aldosterone and the MR to not only vascular events but also glial and neuronal processes in both healthy and diseased retina.…”
Section: Perspectivesmentioning
confidence: 99%
“…1 Extrarenal pathophysiological effects of this hormone have been characterized, extending its actions to the CV system, the brain, the adipose tissue, the skin, and the eye. [2][3][4][5] Inappropriate MR activation has been shown to promote cardiac fibrosis in experimental models 6,7 The Randomized Aldactone Evaluation Study, 8 Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study, 9 and Eplerenone in Mild Patients Hospitalization and Survival Study in Heart Failure 10 clinical trials have demonstrated that the addition of the MR antagonists spironolactone or eplerenone to standard care markedly reduced the overall and CV mortality in patients with left ventricular systolic dysfunction and mild or severe symptoms of chronic heart failure (HF) or with HF signs after acute myocardial infarction.…”
mentioning
confidence: 99%